2005
DOI: 10.1155/jbb.2005.20
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Analysis

Abstract: Diabetic retinopathy is one of the common complications of diabetes. Unfortunately, in many cases the patient is not aware of any symptoms until it is too late for effective treatment. Through analysis of evoked potential response of the retina, the optical nerve, and the optical brain center, a way will be paved for early diagnosis of diabetic retinopathy and prognosis during the treatment process. In this paper, we present an artificial-neural-network-based method to classify diabetic retinopathy subjects ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
2
7
0
2
Order By: Relevance
“…Also, prognosis of the condition can be determined during the treatment. 13 In the present study, the mean P100 latency in the diabetics was found to be significantly prolonged (105.34±7.11SD) when compared with those in the controls (98.21±0.96 SD) ( Table 4). The above findings are in accordance with similar studies in the past including either Type 1 or Type 2 DM or both, without retinopathy.…”
Section: Discussionsupporting
confidence: 51%
“…Also, prognosis of the condition can be determined during the treatment. 13 In the present study, the mean P100 latency in the diabetics was found to be significantly prolonged (105.34±7.11SD) when compared with those in the controls (98.21±0.96 SD) ( Table 4). The above findings are in accordance with similar studies in the past including either Type 1 or Type 2 DM or both, without retinopathy.…”
Section: Discussionsupporting
confidence: 51%
“…In reviewing the literature on retinal image analysis, most progress is in the automated grading process with the goal of replacing the high resources used in current manual grading. In general, the use of computers to aid the detection of retinopathy has been accomplished in as many different ways as there are groups performing the work 90–101 . The use of neural networks that try and ‘teach’ computing systems to recognise patterns has not yet achieved a high enough sensitivity and specificity to be used The simplest algorithms are those that differentiate between a disease and a no disease state.…”
Section: Vision and Challenges For The Futurementioning
confidence: 99%
“…[135][136][137] Results of automated grading to diagnose retinopathy have also been mixed, although some approaches have produced encouraging results. [138][139][140][141] Risks in adopting computer-aided retinopathy detection include unknown algorithm lesion sensitivity and specificity, the possibility of false negatives, and/or missed referable cases.…”
Section: Appendix 3: Computer-aided Detectionmentioning
confidence: 99%